Some physiological aspects of yield in cassava - Cock, James H. (International Center for Tropical Agriculture, 1973)
Results are presented of various trials with cassava. The importance of DM production and factors affecting it, such as LAI and leaf inclination, are discussed. The relative importance of DM production and its distribution, particularly in relation to spacing, are reviewed. The author suggests a plant ideotype based on these observations. (AS)